IL-2 and gene-therapy of cancer - Bubeník, Jan (International journal of oncology, 1993)
The toxicity of high IL-2 doses required for therapy of generalized neoplasms limits at present the large-scale application of IL-2 treatment to the management of cancer. In 1988, it was proposed that insertion of a cloned IL-2 gene into the genome of somatic cells, followed by transfer of the genetically engineered cells constitutively producing IL-2 to the vicinity of the growing tumour, may help overcome the problem of the IL-2 toxicity (Bubenik et al, Immunol Lett 19: 279-282, 1988). It has been demonstrated that this novel approach can be utilized for the treatment of tumors growing in syngeneic, allogeneic and xenogeneic hosts and that both local and systemic administration of the genetically engineered somatic cells can substantially inhibit tumour growth. The aim of this article is to review and summarize recent results of the local and systemic transfer of genetically engineered cells and to discuss the prospects and limitations of the IL-2 gene therapy of cancer. The review is primarily focused on IL-2; however, when relevant, the results obtained with other cytokine gene therapy are also briefly discussed.
Keywords: Neoplasms; genetická terapie; nádory; interleukin-2; experimentální nádory; Interleukin-2; Neoplasms, Experimental; Genetic Therapy